MRI Abnormalities and First Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The frequency of MRI-detected brain abnormalities with first febrile seizures (FS) and their association with FS type and with specific features of complex FS were determined in a prospective study at the Pediatric Emergency Department of New York-Presbyterian Children's Hospital, Columbia University, New York.